The Impact of Digital Economy Literacy Strategy Model on Firm Performance of Small Medium Enterprises - Supriadi, Yudi Nur; Desmintari, Desmintari; Resti, Anggi Angga; Siregar, Zulkifli Musannip Efendi (Budapest International Research and Critics University, 2021)
This study aims to find a digital economic literacy strategy model for SMEs in Indonesia and the factors that can influence it by using a technology acceptance model (TAM) approach consisting of beliefs (perception of usability and perceived ease of use) and their impact on the performance of food SMEs companies in Indonesia particularly in the provinces of Banten, DKI Jakarta, and West Java. This study uses a quantitative method with a sample of 200 SMEs companies using Smart PLS 3 analysis. The results of this study indicate that there is a gap from the absence of the influence of perceived usefulness on firms performance, the results are negative. While perceived usefulness, digital economic literacy is very positive and has an effect on SMEs firms performance. The novelty in this research is finding a new model of strategy model for implementing digital economy literacy, its impact on improving the firms performance of SMEs Food companies.